Автоматизація захисту інформаційного середовища України програмними агентами інтелектуального моніторингу - Голуб, Сергій; Химиця, Наталія; Голуб, Марія (Видавництво Львівської політехніки, 2025)
The use of information technology of intelligent monitoring for the purpose of automating the protection of the information environment of Ukraine is described. Automation of the protection of the information environment is ensured by the continuous operation of software agents separately and as part of virtual robots. The paper describes software agents of various purposes, structures and methods for building their agent models. The features of building software agents for intelligent monitoring of messages in social networks are highlighted. The process of consolidating the results of performing agent tasks related to the intelligent analysis of printed texts, audio messages, photos and videos is described.
Keywords: Інформаційне середовище; інтелектуальний моніторинг; програмний агент; консолідація інформації